Solve each system. Then drag each one to the column headed by a point which could be its solution. (5,y) or (x,2)
2x-2y=12
-2x-3y=-22

2x-6y=10
x+8y=5

3x-y=-5
x+4y=7

x+y=2
2x+y=13

Respuesta :

2x - 2y = 12
-2x - 3y = -22
solution could be (x,2)
===============
2x - 6y = 10 
x + 8y = 5
solution could be : (5,y)
==============
3x - y = -5
x + 4y = 7
solution could be : (x,2)
=============
x + y = 2
2x + y = 13
solution could be : neither....is this one written correctly ?

Answer: system 2 (5,0)        and                        system 3   (-1 2)

             2x-6y=10                                                      3x-y=-5

                x+8y=5                                                      x+4y=7

                             

Step-by-step explanation:

Solve each system. Then drag each one to the column headed by a point which could be its solution. (5,y) or (x,2)

system 1

2x - 2y =12          

-2x-3y = -22

solve simultaneous equation

2x - 2y =12          

-2x-3y = -22

add the equations gives

2x +(-2x) =0

-2y+(-3y) =-5y

12+ (-22) = -10

-5y =-10

y =2

2x -2(2) =12

2x-4 =12

2x = 12+4

x= 16/2 =8 x=8 and y =2 = (8,2)

system 2

2x-6y=10  *(-1) = -2x + 6y =-10

x+8y=5 *(2)    = 2x + 16y =10 add the equations

22y =0 y =0

x : 2x - 6(0) =10

x = 10/2 = 5

(5, 0)

 system 3

  3x-y=-5  *(-1) = -3x + y =5

  x+4y=7 * (3) = 3x + 12y = 21

add the equations = 13y = 26  y = 2

3x -2 =-5 = 3x = -3 =x =-1

(-1 2) answer

system 4

x+y=2   *(-2) = -2x -2y = -4

2x+y=13 *(1) = 2x +y = 13

add the two equations = -y =9

y = -9

substitute 2x-9= 13= 2x =22 x =11

(11 -9)